2017
DOI: 10.1515/hsm-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Review of Superfinishing by the Magnetic Abrasive Finishing Process

Abstract: Recent developments in the engineering industry have created a demand for advanced materials with superior mechanical properties and high-quality surface finishes. Some of the conventional finishing methods such as lapping, grinding, honing, and polishing are now being replaced by non-conventional finishing processes. Magnetic Abrasive Finishing (MAF) is a non-conventional superfinishing process in which magnetic abrasive particles interact with a magnetic field in the finishing zone to remove materials to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
0
28
0
1
Order By: Relevance
“…This can be concluded that each amount of diamond paste (50, 200, and 400 mg) have a significant effect on the improvement in surface roughness. Figure 12 shows the variations of diameter against processing time, which analytically showed that the following (5), (1), and (6) equations with linear characteristics within stable region of diameter changes be extracted as for cases where weights of diamond grains are 50 mg, 200 mg, and 400 mg. There is little significant difference in their slopes.…”
Section: Effect Of the Weight Of Diamond Pastementioning
confidence: 99%
See 1 more Smart Citation
“…This can be concluded that each amount of diamond paste (50, 200, and 400 mg) have a significant effect on the improvement in surface roughness. Figure 12 shows the variations of diameter against processing time, which analytically showed that the following (5), (1), and (6) equations with linear characteristics within stable region of diameter changes be extracted as for cases where weights of diamond grains are 50 mg, 200 mg, and 400 mg. There is little significant difference in their slopes.…”
Section: Effect Of the Weight Of Diamond Pastementioning
confidence: 99%
“…To keep pace with the trend, the machining field adopts more advanced methods for processing materials, such as grinding, polishing, lapping, superfinishing, honing, burnishing, etc. [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For an arbitrary position, FN and FT can be expressed as the sum of two forces Fx along the direction of the magnetic force line and Fy along the magnetic equipotential lines Fx and Fy can be expressed by the following equations [28]: behavior in the absence of a magnetic field source and solid like behavior in the presence of a magnetic field. On the microscopic scale, the van der Waals and magnetic forces are pervasive and must be balanced by coulombic forces by applying a surfactant that attaches to magnetic particles thus stabilizing the magnetic fluid [29], [30].Moreover, the carrier fluid has to be compatible with the surfactant to ensure the stability of the colloid.…”
Section: Magnetic Polishingmentioning
confidence: 99%
“…This brush applies two forces on the surface of the workpiece namely: a normal force (FN) packs the magnetic abrasive particles against the surface of the workpiece and is also responsible for the micro indentations on the surface. The tangential force (FT) is a result of the movement of the flexible magnetic brush and is responsible for the microchipping of the asperities of the workpiece surface[28].…”
mentioning
confidence: 99%
“…However, ion-implantation equipment is highly expensive, the atmosphere used is toxic and the depth of ion implantation is difficult to control. In recent years, some scholars found that magnetic abrasive finishing (MAF) has a significant impact on the surface processing of the difficult-to-machine profiles [9,10]. However, the diameter of titanium alloy wire is too small, making it crucial to ensure that the magnetic abrasive has enough grinding pressure on titanium alloy wire.…”
Section: Introductionmentioning
confidence: 99%